The Improving Speaking Skill through Information Gap Activities at Second Semester of Management Study Program at Panca Marga University in 2021/2022 Academic Year: English - siti masluha (Prodi Tadris Bahasa Inggris, 2023)
Speaking is the highest target in English language because speaking as the basis of communication which becomes a function in learning. There are many kinds of technique to improve speaking skill, such as information gap technique. The researcher wants to find out whether using information gap activities can improve the students’ speaking skills and analysing the classroom situation when this technique is implemented in speaking class. This research used collaborative classroom action research and composed for three cycles following the procedures of action research, namely planning, action, observation, and reflection. The researcher uses instrument of observations, lists, tests, and questionnaire to collect the data. The data obtained was presented in two ways, they are qualitative and quantitative. The findings showed that IGT activities were effective to improve the speaking skill of the learners in class activities. It can be seen from each cycle by the rise in the students’ mean scores in the test result, 59.8 in the first cycle, 69 in the second cycle, and 81, 8 in the third cycle. In other hand, the improvements also based on the results of the observation that showed positivity and good responses from the learners. From the questionnaire results. it was gotten that the means score for the students’ perception was 3,72. It means that the students give positive response for the implementation of this technique.